Integrating Electric Vehicle Technology into Automotive Education Curricula in Colleges of Education in Nigeria: Challenges and Opportunities - Gwana, Bawa Haruna; Sule, Samaila Yerima (ALSYSTECH Journal of Education Technology, 2024)
The main purpose of the study was to integrate electric vehicle technology into Automotive Education Curricula in Colleges of Education in Nigeria with focus on the challenges and opportunities. The study which adopted a descriptive survey research design was conducted in northeast Nigeria and had three research questions. The population of the study was 395 comprising 248 lecturers in Automobile Technology Education from 8 Colleges of Education in the Northeast and 147 industry professionals whose industries are registered with the Corporate Affairs Commission as well as the Ministry of Commerce and Industries in the various states of the Northeast. The study adopted simple random sampling technique which Krejcie and Morgan (1970) sample size table and 191 respondents were selected. A structured questionnaire developed by the researcher titled: "Automobile Electric Vehicle Technology Integration Questionnaire, (AEVTIQ)" was used as instrument for data collection. The instrument was validated by three experts and a reliability index of 0.89 was obtained using Cronbach Alpha. Mean statistic was used to answer the research questions. Findings of the study revealed that the content needed for inclusion include Electric Powertrain Systems, Battery Technology and Management, Charging Infrastructure and Technology, Emerging Technologies and Trends, and Thermal Management Systems. Based on the findings, the study recommended that the NCCE should as a matter of urgency update and enrich the existing curriculum to incorporate comprehensive training on EV technology, covering key areas such as electric powertrain systems, battery management, and charging infrastructure.